Production of human interferon alfa 2b in plants of Nicotiana excelsior by Agrobacterium-mediated transient expression - Sindarovska, Y.R.; Gerasymenko, I.M.; Sheludko, Y.V.; Olevinskaya, Z.M.; Spivak, N.Y.; Kuchuk, N.V. (Цитология и генетика, 2010)
Human interferon α2b gene was transiently expressed in Nicotiana excelsior plants. Fusion with N. plumbaginifolia calreticulin signal peptide for improved apoplast targeting and carrying out the expression under optimized conditions resulted in maximal interferon activity of 3.2 • 10³ IU/g fresh weight (FW) with an average of 2.1 ± 0.8 • 10³ IU/g FW. It proves that N. excelsior is a suitable host for Agrobacterium-mediated transient expression of genes encoding physiologically active human proteins. The transient expression conditions optimized for GFP marker protein were confirmed to be preferable for hIFN α2b.